The School Culture in the Context of the Hofstede's Culture Classification Investigation on Aphorisms - Yılmaz TONBUL; Özden ÖLMEZ CEYLAN (Anı Publishing, 2021)
Culture has an important role in the formation and development of the basic values of a society. Considering that schools are a means of culturing, understanding and developing school culture is very important. With this in mind, this study aimed to determine the place of aphorisms in the school corridors in Hofstede's cultural classification and to prepare a proverbial proposal package for use in schools. The 87 aphorisms, obtained from 80 schools in the research, were grouped according to Hofstede's classification with descriptive analysis, then content analysis of themes in which aphorisms were concentrated was done. It was seen that most emphasis is placed on long-term orientation and least emphasis is placed on high power distance and uncertainty. When the aphorisms were examined thematically, it was seen that emphasis is placed on the themes of "education, teachers, reading habit, being hardworking, love of homeland and science". The themes: love, peace, benevolence, cooperation, etc. can be added to the previous ones. Also, aphorisms can be diversified by selection among artists, scientists, thinkers, and writers who are leaders locally and all over the world. Comparisons can be made by carrying out similar studies in different cities. It is recommended that a study that takes into account the opinions of the teachers and administrators be carried out.